ANTIBIOGRAM PROFILE AND BIOFILM FORMING POTENTIAL OF PSEUDOMONAS SPECIES ISOLATED FROM VARIOUS CLINICAL SPECIMENS - Cp, Jamsheera; Suman, Ethel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study aimed at finding the resistance pattern of Pseudomonas aeruginosa and other Pseudomonas species isolated from various clinical specimens in the laboratory. Methods: A total of 150 isolates of different species of Pseudomonas obtained from various clinical specimens processed at the Microbiology laboratory of Kasturba Medical College, Manipal Academy of Higher Education, were taken for this study. Antibiotic susceptibility testing was performed by Kirby-Bauer disc diffusion method and interpreted according to the CLSI guidelines. Biofilm assay was performed by modified O'Toole and Kolter method. The results were analyzed using SPSS 17.0 and Student's unpaired t-test, Kruskal–Wallis, Mann–Whitney, ANOVA, and Chi-square test. p<0.05 was considered statistically significant. Results: Increased resistance was observed by P. aeruginosa to cefotaxime, cotrimoxazole, levofloxacin, ofloxacin, and ticarcillin clavulanate. There was also a good correlation between antibiotic resistance to aztreonam, netilmicin, and ceftazidime and biofilm production. Results of the present study, therefore, demonstrated the occurrence of resistance to various antipseudomonal agents among the biofilm-producing P. aeruginosa isolates. Conclusion: The present study may help in assessing the seriousness of drug resistance caused by biofilm formation in P. aeruginosa and devise strategies through antibiotic policies to minimize such problems.